Parate Executie Polemic: The Nature of the Authority to Sell Creditors for Objects of Collateral Rights - Shohib, Muslim; Abid Zamzami (Universitas Islam Malang, 2023)
Execution of collateral objects is basically uncomplicated. The holder of the first Mortgage is also entitled to carry out direct execution of the object of the Mortgage that is used as collateral because in addition to the deed of Mortgage it also functions as proof of the existence of a Mortgage. Mortgage is a guarantee institution for land rights in the codification of national land law since the Mortgage Law was promulgated on April 9, 1996 , Mortgage rights function to provide protection for certain creditors and certain positions. where the deed is affixed with the irah-irah